Measuring the amplitude-time characteristics of a pulsed high-intensity gamma radiation acceleratorVarian Clinac 600C aCdTe detector - Grigoryev, A. N.; Bilyk, Z. V.; Litvinov, Yu. V.; Cherniavskiy, I. Yu.; Polyansky, N. E.; Snarenky, V. P.; Samofalov, I. A.; Voronkin, E. F.; Sosnutska, O. O.; Petrukhin, S. Yu.; Suchkov, G. M.; Bilyk, N. G.; et al. (STC "Institute for Single Crystals", 2019)
Measurements of the amplitude-time characteristics of a high-intensity pulsed gamma radiation accelerator Varian Clinac 600C with photon energy from 1 to 6 MeV on the equipment using a CdTe detector in both current and pulse modes have been carried out. It is shown that the operation of the CdTe detector in the current mode allows one to control the frequency of the accelerator pulses, and the operation of the CdTe detector in the pulse mode allows for determining the dose in each pulse with an error of 0.06 %. Monitoring the operation of the accelerator Varian Clinac 600 C shows that the pulses come in batches; within the batch, the pulse repetition period corresponds to a specified frequency at the accelerator, while the repetition period of the batches differs from the specified frequency. Dose control in the pulses showed its 5 % excess over the average value during the first 2.5 s of the accelerator operation, whereas during the last 2 s, the dose reduction by 1.8 % was observed.
Вимірювання амплітудно-часових характеристик імпульсного високоінтенсивного гамма-випромінювання прискорювача Varian Clinac 600C дитектором aCdTe
Keywords: linear accelerator; pulsed gamma radiation; telluride cadmium detector; pulse frequency